Sistem komunikasi Indonesia - Panuju, Redi, 1964- (Yogyakarta : Pustaka Pelajar, 1997)
Characteristics of the Indonesian communication system.
Includes bibliographical references and index.
Keywords: Communication -- Social aspects -- Indonesia; Mass media -- Social aspects -- Indonesia